THE INDEPENDENT STATE COMMISSION IN INDONESIA: A COMPARATIVE REVIEW OF ITS INSTITUTIONAL ASPECTS - Ramadani, Rizki; Arifin, Muhammad Ya'rif (Institut Agama Islam Negeri Bone, 2023)
The establishment of the Independent State Commission and other non-structural institutions was one of the alterations in the structure of the Indonesian constitution during the transition era and after the 1945 Constitution was amended. It is not uncommon for these Commissions to face criticism and controversy due to their autonomous authority and independence from the major branches of power. The objective of this research is to examine and describe the primary traits of such an institution in order for it to be recognized as an Independent State Commission by comparing it to the concept and best practices in the United States. As well as to justify the legitimacy of its position within the Indonesian constitutional framework. As a doctrinal legal research, this study uses a conceptual and legal comparative approach to secondary data presented in a descriptive-analytical manner. The findings revealed that the independent State Commission's two key characteristics were its independence from the executive organsÂ and its autonomous-regulatory power. In terms of legal position, the classical trias politica perspectives need be modified as the Independent State Commission is now viewed as a new branchÂ of government under a new separation of powers framework.